2015
DOI: 10.1016/j.jhep.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 – A key factor and therapeutic target in liver disease

Abstract: Being the largest internal organ of the human body with the unique ability of self-regeneration, the liver is involved in a wide variety of vital functions that require highly orchestrated and controlled biochemical processes. Increasing evidence suggests that microRNAs (miRNAs) are essential for the regulation of liver development, regeneration and metabolic functions. Hence, alterations in intrahepatic miRNA networks have been associated with liver disease including hepatitis, steatosis, cirrhosis and hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
399
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 510 publications
(421 citation statements)
references
References 125 publications
18
399
1
3
Order By: Relevance
“…The discrepancies between different studies may arise from variability in technical procedures from sampling, or the use of different normalization controls or control tissues used for normalization (healthy liver or adjacent non-tumor tissue) [32] or may be due to the small patient population [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancies between different studies may arise from variability in technical procedures from sampling, or the use of different normalization controls or control tissues used for normalization (healthy liver or adjacent non-tumor tissue) [32] or may be due to the small patient population [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found a negative correlation of miRNA-122 with serum HCV RNA, matching with Marquez et al [21] who found that miRNA-122 expression was altered in HCV-infected liver, and miRNA-122 level was inversely correlated, with viral load, fibrosis and serum liver transaminase levels. A possible explanation for this inverse relation is that, counter-intuitively, the beneficial role of miRNA-122 for the virus in vitro does not translate into a positive correlation between its expression and HCV load in patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…miR-122a was extensively studied after the discovery that it may modulate Hepatitis C Virus (HCV) mRNA expression, making it a potential target for antiviral intervention (Jopling et al, 2005). It has been shown that miR-122a is engaged in many liver diseases, like cancer, hepatitis, steatosis and cirrhosis (Bandiera et al, 2015). Furthermore, miR-122a is associated with various metabolic processes, including cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miRNA-122 expression could be decreased in Huh7.5.1 cells transfected with HCV core protein, which corresponds with our results emphasizing the possible role of miR-122 in fibrogenesis and liver cirrhosis Ezzat et al, 2014). Furthermore, other studies in mouse HSCs have shown that the overexpression of miRNA-122 reduced the collagen level, and lower ECM deposition is an indicator of less liver fibrosis related diseases (Jopling, 2008;Bandiera et al, 2015). Furthermore, our achievements also indicated that, while both versions of NS3 proteins downregulated miR-122, a measurable difference between protease competent and protease mutated forms was observed as is indicated by the more but not fully dependent role of protease in this function (P >0.01).…”
Section: Discussionmentioning
confidence: 99%